Comparative study on metabolite level in tissue-specific human mesenchymal stem cells by an ultra-performance liquid chromatography quadrupole time of flight mass spectrometry - Lee, Seul Ji; Yi, Tac Ghee; Ahn, Soo Hyun; Lim, Dong Kyu; Kim, Si na; Lee, Hyun Joo; Cho, Yun Kyoung; Lim, Jae Yol; Sung, Jong Hyuk; Yun, Jeong Ho; Lim, Johan; Song, Sun U.; et al. (Analytica Chimica Acta, 2018)
Mesenchymal stem cells (MSCs) are a promising therapeutic option for cell-based therapy due to their immunomodulatory and regenerative properties. They can be isolated from various adult tissues, including bone marrow, fat, dental tissue, and glandular tissue. Although they share common characteristics, little is known about the biological differences between MSC populations derived from different tissues. In this study, we used MS to compare the endogenous metabolite level in the human MSCs originating from the bone marrow, adipose tissue, periodontal ligaments, and salivary glands. Using an optimized metabolomics technique, we verified that human MSCs exhibit differences in the endogenous metabolite level depending on their source material, while the multivariate analysis showed that 5 lysophosphatidylcholines and 3 lysophosphatidylethanolamines can serve as markers for the discrimination between MSC sources and may be related to differences in their differentiation capacity. These results may significantly contribute to further mechanistic studies on the MSCs and provide novel insights into the properties and optimal usage of MSCs from different tissues.
Keywords: Adipose derived stem cells; Bone marrow; Mesenchymal stem cell; Periodontal ligament; Salivary glands; Adipose Tissue; Adult; Biomarkers; Bone Marrow Cells; Cell Differentiation; Cell Proliferation; Chromatography, High Pressure Liquid; Female; Humans; Immunomodulation; Lysophosphatidylcholines; Lysophospholipids; Mass Spectrometry; Mesenchymal Stromal Cells; Metabolomics; Multivariate Analysis; Organ Specificity; Periodontal Ligament; Salivary Glands; Adipose-derived stem cell; Bone marrow-derived stem cell; Differentiation; Mesenchymal stem cell; Periodontal ligament-derived stem cell; Salivary gland-derived stem cell